2021
DOI: 10.3389/fcell.2021.651803
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Biomarker Hsa_circ_0126218 and Functioning Prediction in Peripheral Blood Monocular Cells of Female Patients With Major Depressive Disorder

Abstract: IntroductionAlthough major depressive diroder (MDD) has brought huge burden and challenges to society globally, effective and accurate diagnoses and treatments remain inadequate. The pathogenesis that for women are more likely to suffer from depression than men needs to be excavated as well. The function of circRNAs in pathological process of depression has not been widely investigated. This study aims to explore potential diagnostic biomarker circRNA of female patients with MDD and to investigate its role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…It has been hypothesised that circRNAs bind to miRNAs as a chelator and further influence the expression of several factors that influence depression, such as mRNA stability, resulting in depressive-like behaviour [ 143 , 144 ]. The former study demonstrated that microglia transfer a microglia-enriched microRNA, miR-146a-5p, by secreting exosomes to improve neurogenesis and depression-like behaviour.…”
Section: Interconnections Between Ncrnas In Depressionmentioning
confidence: 99%
“…It has been hypothesised that circRNAs bind to miRNAs as a chelator and further influence the expression of several factors that influence depression, such as mRNA stability, resulting in depressive-like behaviour [ 143 , 144 ]. The former study demonstrated that microglia transfer a microglia-enriched microRNA, miR-146a-5p, by secreting exosomes to improve neurogenesis and depression-like behaviour.…”
Section: Interconnections Between Ncrnas In Depressionmentioning
confidence: 99%
“…Emerging studies have shown that circRNAs may be involved in the onset and progression of depression, so they have become a promising new field in the diagnosis of depression. Reports have shown that hsa_circRNA_103636 ( Cui et al, 2016 ), hsa_circ_0126218 ( Bu et al, 2021 ), circFKBP8 ( Shi et al, 2021 ), circMBNL1 ( Shi et al, 2021 ), and circDYM ( Song et al, 2020 ) might be promising MDD biomarkers, which may further improve the early detection, effective diagnosis, and convenient monitoring of MDD. However, at present, the diagnostic accuracy and specificity of these circRNAs still need to be verified by multicenter and large samples.…”
Section: Involvement Of Circrnas In Cognitive-related Diseasesmentioning
confidence: 99%
“…Nowadays, there are more and more researches on the mechanism of circRNAs generation. In addition to RBP can bind to circRNAs to reduce the regulation of RBP on target genes and affect tumorigenesis (Huang C.-K. et al, 2020;Li et al, 2020;Song et al, 2021), some RBP can also regulate the generation of circRNAs, which also has an important role in tumor development (2016;Liu Z. et al, 2021;Wang et al, 2021d;Wang and Lei, 2021;Yang T. et al, 2021). The translation function of circRNAs is also becoming a hot topic, and the translation initiation mechanism of circRNAs mainly includes cap-dependent, IRES-dependent, m6adependent and small ORF-dependent translation initiation (He L. et al, 2021;Wang X. et al, 2021), and circRNAs encode proteins with the function of suppressing tumor activity and protecting proteins from degradation (Chen C.-K. et al, 2021;Wang et al, 2021d;Ma et al, 2021;Qi et al, 2021).…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Studies have shown that circRNAs are abundant and stable in exosomes, and some circRNAs are more highly expressed in blood than in tissues ( D'Ambrosi et al, 2021 ; Reese and Dhayat, 2021 ; Tian et al, 2021 ; van Zonneveld et al, 2021 ). The high expression and stability of circRNAs in body fluids would be more beneficial for their clinical applications ( Bu et al, 2021 ; Fontemaggi et al, 2021 ; Wang et al, 2021h ; Zhao et al, 2021 ). However, despite the identification of thousands of tissue- and disease-specific circRNAs by RNA-seq ( Kaushik et al, 2021 ; Tian-Zhao et al, 2021 ), the understanding of the mechanism of circRNAs generation and biological functions is limited at this stage.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%